Histiocyte-rich rhabdomyoblastic tumor: rhabdomyosarcoma, rhabdomyoma, or rhabdomyoblastic tumor of uncertain malignant potential? A histologically distinctive rhabdomyoblastic tumor in search of a place in the classification of skeletal muscle neoplasms - Martinez, Anthony P.; Fritchie, Karen J.; Weiss, Sharon W.; Agaimy, Abbas; Haller, Florian; Huang, Hsuan-Ying; Lee, Seungjae; Bahrami, Armita; Folpe, Andrew L. (Modern Pathology, 2019)
Skeletal muscle tumors are traditionally classified as rhabdomyoma or rhabdomyosarcoma. We have identified an unusual adult rhabdomyoblastic tumor not clearly corresponding to a previously described variant of rhabdomyoma or rhabdomyosarcoma, characterized by a very striking proliferation of non-neoplastic histiocytes, obscuring the underlying tumor. Ten cases were identified in nine males and one female with a median age of 43 years (range 23-69 years). Tumors involved the deep soft tissues of the trunk (N = 4), lower limbs (N = 4), and neck (N = 2). Tumors were well-circumscribed, nodular masses, frequently surrounded by a fibrous capsule containing lymphoid aggregates and sometimes calcifications. Numerous foamy macrophages, multinucleated Touton-type giant cells, and sheets/fascicles of smaller, often spindled macrophages largely obscured the underlying desmin, MyoD1, and myogenin-positive rhabdomyoblastic tumor. Cases were wild type for MYOD1 and no other mutations or rearrangements characteristic of a known subtype of rhabdomyoma or rhabdomyosarcoma were identified. Two of four cases successfully analyzed using a next-generation sequencing panel of 170 common cancer-related genes harbored inactivating NF1 mutations. Next-generation sequencing showed no gene fusions. Clinical follow (nine patients; median 9 months; mean 23 months; range 3-124 months) showed all patients received wide excision; four patients also received adjuvant radiotherapy and none received chemotherapy. At the time of last follow-up, all patients were alive and without disease; no local recurrences or distant metastases occurred. We hypothesize that these unusual tumors represent rhabdomyoblastic tumors of uncertain malignant potential. Possibly over time they should be relegated to a new category of skeletal muscle tumors of intermediate (borderline) malignancy.
CRIS-Team WoS Importer:2019-03-15